Diseño del Sistema de Iluminación para la Cancha Sintética del Parque Recreacional Jipiro de la Ciudad de Loja - Sivisapa Aguilera, Aníbal Patricio (2019)
The present project consists of the proposed lighting of the synthetic court of the Jipiro recreational park, which is located in the city of Loja, the sizing was done considering the standard for lighting of sports scenarios UNE-EN 12193, which we allowed to determine the level of illuminance that this sports scenario should have based on the dimensions it has, guaranteeing an efficient lighting design and according to the requirements for this sports scenario. The current sports stage lighting project determined that 400W Tempo 3 RVP351 sodium vapor luminaires show the best option with a total of 162 luminaires, giving a total load to be installed of 64.8 kW so it is decided to install a three-phase 75 kVA transformer. The electrical part of this project was carried out according to the parameters recommended by Empresa Eléctrica Regional del Sur S.A (EERSSA), while the civil works for the creation of wells, ditches, distribution chamber, etc. It was based on what the MEER manual recommends. The grounding system of this project is designed according to the IEEE-80 standard. The required data were provided by the Municipality of Loja, staff working in this sports scenario and field research. The investment amount of 75 448,54 USD is made based on local and national contributions, value that served for the financial economic analysis obtaining the indicators: B/C ratio (1.19), VAN (+ 46 041,71 USD) and TIR (10%). The results of this analysis are favorable, which demonstrates the convenience of project execution.